Effect of Type of Milk and Storage Period on the Quality of Hard Cheese* (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to determine the effect ofstorage period on the chemical composition of hard cheese (“Roomi”),manufactured from cow and goat milks and their blends (1:1). A starterculture 1% of Streptococcus thermophills and Lactobacillus bulugaricusand rennet tablet (one tablet /50 litre milk) were used. The curd wascheddared, salted, moulded, pressed overnight, coated with paraffin waxand stored at 12±2ºC for ripening. The proximate analysis of cheesesreflected changes in total solids, total protein and fat contents towardsripening. Cheese prepared from goat milk recorded higher level of solidsand fat than cow and blend cheeses. Cow cheese showed significantly(P≤0.05) higher level of protein than goat and blend cheeses. The pH ofthe three types of cheeses significantly (P≤0.05) decreased inconcomitance with increase in their titratable acidity of all cheeses. Thesoluble nitrogen content increased significantly (P≤0.05) during ripeningof all cheeses. The ratio of soluble nitrogen to total nitrogen alsoincreased significantly (P≤0.05) during ripening of all cheeses.